DEVELOPMENT OF HUMAN RESOURCES (TEACHERS) TO IMPROVE THE QUALITY OF SMP N 3 SUWAWA. - Nelviyanti Mahmud; Djamila Podungge; Yolanda Ngabito (LP2M Universitas Bina Mandiri Gorontalo, 2025)
The study aims to determine the factors that influence the development of human resources (teachers) to improve the quality of SMP N 3 Suwawa. The data in this research are primary and secondary data. The data sources in this research are informants and documentation. The method in this research uses descriptive qualitative methods with data collection techniques using observation, interviews and documentation. The subjects of this research were four people, namely the principal, deputy principal, and two supporting teachers. The result shows that there are two factors that influence the development of human resources (teachers) in improving the quality of SMP N 3 Suwawa, namely internal and external factors. Several obstacles that are often faced mean that teachers at SMP Negeri 3 Suwawa have not been able to participate in comprehensive development programs. Therefore, this has an impact on improving the quality of SMP Negeri 3 Suwawa.